2020
DOI: 10.1097/dcc.0000000000000440
|View full text |Cite
|
Sign up to set email alerts
|

National Survey of Feeding Tube Verification Practices

Abstract: Background Harm events such as pneumothoraces and pneumonia continue to be associated with feeding tube insertion. Most bedside verification methods are not accurate to discriminate pulmonary from gastrointestinal system. Evidence-based clinical practice guidelines do not support auscultation of feeding tubes in adults, yet auscultation is the most common method used. Objectives Our survey assessed national feeding tube verification practices used by cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Of the 122 nurses who reinserted stylets into feeding tubes, 39% reported using no cleansing method, 21% used an alcohol swab, 15% used tissue/gauze wipe, and 22% rinsed the stylet with water (more than half used tap water vs sterile water) 17 . Six nurses reported using multiple cleansing methods, although it is unknown if these methods were used concurrently 17 . Specific timing of the stylet cleansing (ie, before and/or following stylet reinsertion) was not included in our survey.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 122 nurses who reinserted stylets into feeding tubes, 39% reported using no cleansing method, 21% used an alcohol swab, 15% used tissue/gauze wipe, and 22% rinsed the stylet with water (more than half used tap water vs sterile water) 17 . Six nurses reported using multiple cleansing methods, although it is unknown if these methods were used concurrently 17 . Specific timing of the stylet cleansing (ie, before and/or following stylet reinsertion) was not included in our survey.…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 national US survey showed variation in cleansing methods of reusable stylets by critical care nurses. Of the 122 nurses who reinserted stylets into feeding tubes, 39% reported using no cleansing method, 21% used an alcohol swab, 15% used tissue/gauze wipe, and 22% rinsed the stylet with water (more than half used tap water vs sterile water) 17 . Six nurses reported using multiple cleansing methods, although it is unknown if these methods were used concurrently 17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The American Association of Critical-Care Nurses issued a practice alert on verification of feeding tube placement stating this method should not be used to assess tube placement. Despite this warning, a national survey conducted five years later reported that 76% of health care providers still utilize this auscultation technique (4).…”
Section: Introductionmentioning
confidence: 99%